Possibility of Hermeneutic Conversation and Ethics - Mehmel, Constantin-Alexander (Theoria and Praxis: International Journal of Interdisciplinary Thought, 2016)
In this paper, I aim to defend Gadamer’s philosophical hermeneutics against what I call the radical hermeneutic critique, specifically the critique developed in Robert Bernasconi’s article “’You Don’t Know What I’m Talking About’: Alterity and the Hermeneutic Ideal” (1995). Key to this critique is the claim that Gadamer’s account does not rise to the ethical task of embracing the alterity of the Other, but instead reduces it to a projection of one’s self. The implication is therefore that Gadamer’s philosophical hermeneutics has to be rejected on ethical grounds, as it does not appreciate but assimilates the alterity of the Other. In contrast to this radical hermeneutic critique, I argue that Gadamer’s philosophical hermeneutics can accommodate an Other that is not assimilated but appreciated, on the condition that the unique status of a dialogue with the Other as a person is no longer neglected, as Gadamer does, but instead truly distinguished from a dialogue with the Other as a text.